1993
DOI: 10.1002/jcu.1870210105
|View full text |Cite
|
Sign up to set email alerts
|

Endovaginal doppler flow measurements of the ovarian artery in patients with a normal menstrual cycle and with polycystic ovary syndrome during in vitro fertilization

Abstract: Women with a normal menstrual cycle (n = 21, controls), polycystic ovary syndrome (n = 10) and hypogonadotropic amenorrhea (n = 3) were stimulated with clomiphen-citrate (4th day to 8th day of the cycle) and with human menopausal gonadotropin (8th day to 11th day). The vascular impedance of the ovary carrying the dominant follicles was monitored by endovaginal pulsed Doppler flow measurement. Simultaneously, serum levels of LH, E2 and 17-OHP were assayed. Contrary to controls, women with polycystic ovary syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
3
8
0
1
Order By: Relevance
“…Moreover with a rise in estradiol levels, the PI of the ovarian artery decreased to reach a nadir on the day of ovulation. Patients with PCOS had higher estradiol values during the proliferative phase, and despite hormonal stimulation the blood flow in the patient did not improve [14]. Zaidi et al [15] studied the intraovarian vasculature and found a higher intensity of color flow in the ovarian stroma of patients with PCOS.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover with a rise in estradiol levels, the PI of the ovarian artery decreased to reach a nadir on the day of ovulation. Patients with PCOS had higher estradiol values during the proliferative phase, and despite hormonal stimulation the blood flow in the patient did not improve [14]. Zaidi et al [15] studied the intraovarian vasculature and found a higher intensity of color flow in the ovarian stroma of patients with PCOS.…”
Section: Discussionmentioning
confidence: 96%
“…7,14,18,20,[48][49][50][51][52] Goswamy and Steptoe 14 were the first to report significantly elevated RI and PI values in the uterine arteries of infertile women who had PCOS. The uterine artery RI was found to be inversely related to the intraovarian flow RI in these patients.…”
mentioning
confidence: 99%
“…A diminuição nos índices de resistência arterial é determinada pela neovascularização formada ao redor do folículo dominante e, subsequentemente do corpo lúteo, e pela vasodilatação induzida pelo estradiol nas artérias ovarianas 28 . A hipertensão porta em portadoras de esquistossomose hepatoesplênica não parece impedir que os novos capilares desenvolvidos ao redor do folículo em crescimento, e no corpo lúteo formado posteriormente, diminuam a impedância ao fluxo nos ovários na fase folicular tardia e lútea media 23,28 . Por outro lado, estudando os índices arteriais ovarianos como um todo, não foi observada diferença estatística entre os grupos.…”
Section: Discussionunclassified